Public and pharmacist perceptions towards counterfeit medicine in Lebanon using focus groups - Sholy, Lydia B.; Gard, Paul R.; Williams, Sian; MacAdam, Angela; Saliba, Christiane E. (International Journal Of Community Medicine And Public Health, 2018)
Background: Counterfeit medicine is a product that is deliberately and fraudulently mislabelled with respect to identity or source. The international concern is the risk counterfeits pose for public health. To date, there are no published studies on public and pharmacist perceptions towards counterfeit medicine in Lebanon. Therefore, the aim of the study was to explore participants’ experiences, views and beliefs regarding counterfeit medicine by employing the mixed methods methodology. Methods: The study used four focus groups. The two public focus groups were recruited using the convenience sampling method from two schools in Mount Lebanon. The two pharmacists’ focus groups were recruited by the snowball approach from different pharmacy settings. All participants were above 18 years old. Results: The public and pharmacist focus groups had a total of 24 and 13 participants respectively. Using thematic analysis, themes and subthemes emerged from the discussions, and the common themes between the public and pharmacists were; awareness, trust, corruption and overcoming counterfeit medicine. Conclusions: The findings showed the perceived risk counterfeit medicine pose to individuals and public health. According to focus group participants, the situation is serious and requires more attention from the Ministry of Public Health and Order of Pharmacists. Therefore, the need is to establish strict control on medicine; implement and enforce the law; reactivate the central laboratory; create a counterfeit medicine reporting system, and develop continuous educational programs.